PENDIDIKAN UNTUK KESETARAAN: HAK BERSAMA Education for Equality: Equal Rights - Lailisna, Novi Nur (Musawa Jurnal Studi Gender dan Islam, 2015)
Implementation of the principles of Basic Human Rights in education is an issue on which theÂ  struggle continues, both for males and for females. Islam is an egalitarian religion on this matter as stated in the hadith: â€œAccording to knowledge, it is obligatory for both Muslim males and femalesâ€, (al-Hadist). In the report on education (UIN SGD Bandung, 2008), gender was prioritised, however, discrimination and subordination linger in the interpretations of Islamic verses. Muthtar (YPJ, Topik Empu, 2010) has stated that education in Indonesia remains depressing in terms of the rights of females to education, such that there is a need for a feminist education for marginalised females to increase educational justice and equality for all citizens. 2015 is the year in which education for all is the target of the Millennium Development Goals, which also aim for basic educational access for all, as well as gender equality in primary and secondary schools. Sadli (2010) proposes that in the year that follows, another obstacle must be overcome â€“ the need for equal access to higher education. In a similar vein to the notion that education most simply refers to human demand for knowledge, which starts with the nurturing received from mothers and proceeds throughout life (Life Long Learning), female activists are inspired to promote informal education as an alternative means to becoming educated.Â  Using a prospective approach, this paper outlines educational theory in relation to the rights of females. Further, it looks at how Islam offers educational guidance to females in relation to their roles in the domestic realm (almost 24 hours), and the achievements of the feminist movement in regard to gender and feminist education according to Islam and current Indonesian law. The results of this study offer recommendations which it is hoped will become learning tools and lessons for the critical construction of society. Education, for males and females, is a basic need and human right. Most important is the need to overcome the barriers to education for females.Â  Marginalised females, in particular, bear the right to access to basic, religious and feministÂ  education.